Calagem e adubação fosfatada no crescimento de mudas de mimosa caesalpiniifolia benth. em latossolo vermelho-amarelo - Filho, Raimundo Tomaz da Costa; Valeri, Sérgio Valiengo [UNESP]; da Cruz, Mara Cristina Pessôa [UNESP] (Universidade Federal de Santa Maria, 2013)
This work aimed to evaluate the effects of liming and phosphate fertilizer for the production of sabiá (Mimosa caesalpiniifolia Benth.) seedlings without thorns under a greenhouse. Seedlings 10 days old were transferred to plastic bags containing 2.0 kg of psamitic Dystrophic Red-Yellow Latosol (Typic Haplustox) collected from 40 to 70 cm layer. The experiment was carried out in Teresina county, Piauí state, Brazil, from July to October of 2008. Two liming doses (with and without liming) and five phosphorus doses combined in a 2 x 5 factorial scheme were used. The experimental design used was the randomized blocks with four replications having each plot three seedlings. The calculated lime amount was enough to elevate the base saturation to 50 % and the phosphorus doses were: 0, 30, 60, 90, and 120 mg kg-1 of soil. One seedling per pot was cultivated and the pot dimension was 10 by 23 cm. The evaluated variables were height, diameter, leaves number, leaf area, and shoot and roots dry matter. For the studied soil condition, the liming is not necessary to produce 'Sabiá' seedlings. The application, on average, from 72 to 107 mg kg-1 of P promote, respectively, from 90 to100 % of maximum values of height, diameter, leaf area and shoots and roots biomass.
Liming and phosphate fertilizer on growth of mimosa caesalpiniifolia benth. seedlings in red-yellow latosol
Keywords: Fertilization; Lime; Sabiá; Woody species